Keterampilan Berbicara berdasarkan Rasa Percaya Diri Siswa pada Mata Pelajaran Bahasa Indonesia Kelas III MI Miftahul Huda Sukolilo Kecamatan Jiwan Kabupaten Madiun - Zakiya Fachrunnisa; Ayunda Riska Puspita (AL-THIFL : Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2023)
Good language learning does not ignore language skills. Language skills consist of four parts, namely listening, speaking, reading, and writing skills. Basically everyone has self-confidence. At the time of expressing their opinions, there were students who dared, there were also those who did not dare to express their opinions orally. Confidence is one of the factors that influence speaking skills. The aims of this study were (1) to describe students' speaking skills in class III Indonesian subject, (2) to describe students' self-confidence in class III Indonesian subject, (3) to describe speaking skills based on students' confidence in subject Grade III Indonesian. The approach used is a qualitative approach. The type of research used is descriptive research. Data collection techniques using tests, questionnaires, observations, interviews, and documentation. The data analysis technique uses data reduction obtained from the results of the assessment of the speaking skill test and the results of the self-confidence questionnaire. Researchers present data in the form of narrative. In this study, the results obtained were (1) students' speaking skills in the very good category were 3 students, 10 students in the good category and 3 students in the sufficient category. (2) students' self-confidence in the very high category of Indonesian subjects was 3 students, 10 students in the high category and 3 students in the sufficient category. (3) the results of speaking skills based on students' self-confidence, namely that students who have very high self-confidence have very good speaking skills, students who have high self-confidence have good speaking skills, and students who have sufficient self-confidence have sufficient speaking skills.